The Effect of Principal Leadership Style and Teacher Performance on Student Learning Achievement at MTs. NW Kalijaga - Sufi Laelawati; Rudi Hariawan; Muhammad Iqbal (Universitas Pendidikan Mandalika, 2025)
This study aims to determine the influence of school principals' leadership style and teachers' performance on students' academic achievement at MTs. NW Kalijaga. The background of this research is based on the important role of school principals in creating a conducive learning environment and the effectiveness of teachers' performance in delivering learning materials. This research uses a quantitative approach with a survey method and multiple linear regression analysis. The sample consisted of 100 students selected using proportional random sampling from the population of 7th and 8th grade students. The results of the analysis show that partially, the leadership style of school principals has no significant effect on students' academic achievement (t = 1.105; sig. = 0.272), and neither does teacher performance individually (t = -1.906; sig. = 0.060). However, simultaneously, the leadership style of school principals and teacher performance have a significant effect on students' academic achievement (F = 3.108; sig. = 0.049). The coefficient of determination (R²) value is 0.060, indicating that the contribution of the two independent variables to students' academic achievement is only 6%. Although the contribution is relatively low, the F-test results show a statistically significant combined effect). Key Words: Leadership Style, Teacher Performance, Student Academic Achievement. Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh Gaya Kepemimpinan Kepala Sekolah dan Kinerja Guru Terhadap Prestasi Belajar Siswa di MTs. NW Kalijaga. Latar belakang penelitian ini didasari oleh pentingnya peran kepala sekolah dalam menciptakan lingkungan belajar yang kondusif serta kinerja guru dalam menyampaikan materi pembelajaran secara efektif. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei dan analisis regresi linear berganda. Sampel penelitian berjumlah 100 siswa yang ditentukan dengan teknik proportional random sampling dari populasi siswa kelas VII dan VIII. Hasil analisis menunjukkan bahwa secara parsial, gaya kepemimpinan kepala sekolah tidak berpengaruh signifikan terhadap prestasi belajar siswa (t = 1,105; sig. = 0,272), demikian pula kinerja guru tidak berpengaruh signifikan secara individual (t = -1,906; sig. = 0,060). Namun, secara simultan gaya kepemimpinan kepala sekolah dan kinerja guru memiliki pengaruh yang signifikan terhadap prestasi belajar siswa (F = 3,108; sig. = 0,049). Nilai koefisien determinasi (R²) sebesar 0,060 menunjukkan bahwa kontribusi kedua variabel bebas terhadap prestasi belajar siswa hanya sebesar 6%. Meskipun kontribusi tersebut tergolong rendah, namun hasil uji F menunjukkan adanya pengaruh secara bersama-sama yang signifikan secara statistik). Kata Kunci: Gaya Kepemimpinan, Kinerja Guru, Prestasi Belajar Siswa.